IN VIVO CHARACTERIZATION OF LESS PAINFUL PROPOFOL NANOEMULSION USING PALM OIL FOR INTRAVENOUS DRUG DELIVERY - PRASETYO, BAYU EKO; AZMI, NORAZRINA; SHAMSUDDIN, AHMAD FUAD (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of present work was to evaluate the effectiveness of propofol in nanoemulsion based palm oil that called as NEMS™, which was a choice of anesthetic drug to induce and maintenance general anesthesia to reduce pain on injection activity and also to evaluate the in vivo characterization of propofol in NEMS™. Methods: Preparation of propofol nanoemulsion using NEMS™ technology has been performed for propofol 1% in NEMS™ (P1%), and propofol 2% in NEMS™ (P2%). Determination of free propofol concentration in aqueous phase was conducted using HPLC and rat paw lick test was evaluated as in vivo test to assay the intensity of pain on injection site. The sleep recovery test was conducted to evaluate the pharmacological effect and erythrocyte hemolysis test also conducted to ensure the safety of propofol in NEMS™. All of the test results were compared with Diprivan®1% as a positive standard. Results: The contents of free propofol in formulation P1% and Diprivan®1% in aqueous-phase were 6.20±0.03 µg/ml and 15.02±0.33 µg/ml, respectively (*P<0.05). The rat paw lick test showed that the formulation P1% was significantly (*P<0.05) less painful when compared to Diprivan®1%. There were no significant differences in pharmacological effect for all of the formulations (*P>0.05). The erythrocyte haemolysis test show that all formulation still safe for our blood. Conclusion: Palm oil can be used as a carrier for propofol and it was successfully reduced the free propofol contents and the intensity of pain on injection site in rats.